THE ROLE OF JAVA CABE (Piper retrofractum vahl.) ON TRAUMATIC ULCER TREATMENT : Peran Cabe Jawa (Piper Retrofractum Vahl.) Dalam Menanggulangi Ulkus Traumatikus - Della Yudi Ardana; I Gusti Ngurah Putra Dermawan; Ni Nyoman Gemini Sari (Interdental Jurnal Kedokteran Gigi (IJKG), 2022)
Introduction: Dental and oral diseases in Indonesia still need attention. Theoral cavity is a place for microorganisms that cause infection that can affectthe general state of health in which the oral mucosa serves as a protector ordefense to protect the oral cavity from disease. One of the most common oral mucosal diseases is traumatic ulcer. Review: Traumatic ulcer is an oraldisease that often found in the community and often underestimated.Traumatic ulcer is a pathological condition characterized by loss of epithelial tissue due to sloughing of necrotic and widespread inflammatory tissue in thelamina propria, which caused by trauma, for example is when wearingdenture wings too sharp, causing ulcers. The etiology of traumatic ulcers arethermal, chemical, and mechanical trauma. The common location oftraumatic ulcers occurs in the labial/buccal mucosa, palate, and tongue.Needed for appropriate treatment for treat traumatic ulcers. Discussion: Fortreat traumatic ulcer, parts that can be used from the Javanese chili plant arethe fruit, leaves, and roots for treating bad breath, as antipyretic, antioxidant,antibacterial, and etc. Javanese chili (Piper Retrofractum Vahl.) hascompounds that act as antioxidants and antibacterial, namely flavonoid whichtrigger the growth of epithelial tissue in wound tissue, and piperine whichinhibits cyclooxygenase which has an effect on reducing leukocytes thatoccurs in traumatic ulcers. Conclusion: Javanese chili herbs contain activecompounds such as flavonoid and piperine which can heal traumatic ulcers.